“Deep Cover”: Identities and ethics in martial arts fieldwork (Revista de Artes Marciales Asiáticas, 2019)
Qualitative research in the social sciences typically requires a personal engagement with resource persons. The widely used participant-observation method requires that the researcher assume as far as possible the role of community member. Even when participant observation is not the chosen method, group members assign identities to investigators. Role assignment in martial contexts may range from the “intruder” who disrupts ongoing events (e.g., outsiders may not see “secret techniques”) to one who is allowed insider access, usually after having gone through some test or rite of passage. Data collected in “natural context” is ideal. The primary problem here is that act of observation inevitably changes phenomena under examination. The most effective means of gathering information in a natural context is by engaging in what is known in the Intelligence community as “deep cover” actually joining a community for the purpose of secretly gathering information. This, of course, brings with it serious ethical dilemmas. While it is clear that we must all address the issue of transparency vs. efficiency, most decisions actually are made on a case by case basis. I suggest that it may be time to develop a general set of guidelines to help us keep faith with informants and accomplish our academic goals of accurately depicting the martial cultures with which we engage.